Perancangan Film Animasi Pendek Sebagai Media Promosi (Studi Kasus Rudang Hotel and Resort) - Surya; Yunita Sari Siregar; Nur Wulan (LKP Unity Academy, 2023)
The massive development of the animation world since the 2000s shows that local animation has not been able to compete with the existence of foreign animation. The development of information technology encourages the birth of promotional media that are increasingly attractive, creative, and innovative, such as promotional media in the form of animation. This research was conducted by designing an animated promotional video for hotels and resorts. In making animated promotional videos for Rudang Hotels and Resorts using the Adobe Animate application, researchers used UML (Unified Modeling Language), namely use case diagrams and activity diagrams. In designing animation there are 3 stages that must be done, namely the Pre-Production Stage, Production Stage and Post-Production Stage. Animated advertisements about Rudang Hotels and Resorts using Adobe Animate software and made into 2-dimensional animation. The design of promotional advertisements about Rudang Hotels and Resorts consists of text, studio, animation, and sound designs to invite the public to know more about Hotels and Resorts. With this promotional advertisement, it is hoped that hotels and resorts will benefit by attracting public attention. As a recommendation, for readers, I hope this thesis can be a reference for the design of promotional advertisements. This thesis includes the design and analysis of systems for making promotional advertisements. Rudang Hotels and Resorts can take advantage of this promotional advertisement as well as possible.